The Effect Of Good Corporate Government On Earning Management In Trading Companies Listed On The Indonesia Stock Exchange - Mahmudah, Annita (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2021)
Trading company is a company that purely only sells products whoseproducts have been provided by suppliers or manufacturers with the aimof creating added value. Trading company financial reports must bereported annually. The company has the goal of increasing profits,therefore company leaders try to manage earnings. To achieve this,researchers conducted mini research on good corporate government andearning management. The result of this research is that GCG (GoodCorporate Governance) does not have a significant effect on earningmanagement